Extended reality technology – a new component in industrial engineering and production systems - A. S. Zuev; M. A. Makushchenko; M. E. Ivanov; E. S. Merkulov (Российский технологический журнал)
Extended (virtual, augmented and mixed) reality technology gets considered as a new universal component of production (industrial) engineering’s methodological basis, receiving the possibilities for wide use in both extensive and intensive development of carrying and other branches of the fourth, fifth and the forming nucleus of the sixth technological wave. The article gives grounds for the role and place of this kind of technology in contemporary technological processes and production systems (including the flexible, small-volume and discrete production), and in the context of cyberphysical systems and the incoming fourth industrial revolution. The authors describe underline the set of tasks that are universal for a wide range of branches in any national economy, that can be most efficiently completed in terms of the current and prognosed level of development of man-machine interaction can be provided for as a result of using VR, AR and MR technologies. Based on the comparison of implementation principles and examples of applied implementation, the article gives grounds for term correspondence and opportunities of use of “extended reality technology”. The authors have made and explained the conclusion on practicability of integrating extended reality technology based on a universal hardwaresoftware complex that provides VR, AR and MR services corresponding to the composition of a given task within the technological process or the operating mode chosen by a user. The article gives descriptions of task assignments, terms of conduct and results of experiments on designing and testing extended reality interactive environments performed at the institute of information technology RTU MIREA in 2019–2020.